2001
DOI: 10.1097/00007632-200104010-00020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Exercise and Spinal Manipulation for Patients With Chronic Neck Pain

Abstract: For chronic neck pain, the use of strengthening exercise, whether in combination with spinal manipulation or in the form of a high-technology MedX program, appears to be more beneficial to patients with chronic neck pain than the use of spinal manipulation alone. The effect of low-technology exercise or spinal manipulative therapy alone, as compared with no treatment or placebo, and the optimal dose and relative cost effectiveness of these therapies, need to be evaluated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
208
5
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(232 citation statements)
references
References 22 publications
11
208
5
8
Order By: Relevance
“…In a recent randomized clinical trial (Bronfort et al, 2001) substantial improvement in the neck disability index was observed in the groups, but no significant differences between groups reported (p > 0.05). In contrast to these findings, our study demonstrated that experimental group had significantly improved in neck disability score (p < 001) than isometric group after three weeks of treatment.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In a recent randomized clinical trial (Bronfort et al, 2001) substantial improvement in the neck disability index was observed in the groups, but no significant differences between groups reported (p > 0.05). In contrast to these findings, our study demonstrated that experimental group had significantly improved in neck disability score (p < 001) than isometric group after three weeks of treatment.…”
Section: Resultsmentioning
confidence: 81%
“…Couch, Hot packs, Standard Inclinometer, Visual Analogue Scale (VAS) and Neck disability index (NDI) were the instruments used during the study ((Youdas & Garret, 1992;Cynthia, 1998;Bronfort, et al, 2001;Werner, 2001) The study protocol was reviewed and approved by the Institutional Research Committee of Department of Therapies and Health Sciences, Faridabad. After the process of screening, examination and informed consent, the patient rated their pain intensity on Visual Analogue Scale, functional outcomes on Neck Disability Index and followed by an inclinometer examination of cervical Range of Motion.…”
Section: Methodsmentioning
confidence: 99%
“…Gong et al 4) reported that cervical mobilization performed for 40 students with abnormal posture of the cervical spine significantly improved FHP. Bronfort et al 10) also reported that spinal manual therapy combined with exercise, used to treat 191 chronic neck pain patients, resulted in significantly increased ROM. In another study, in which traction combined with cervical manipulation was used to treat patients with reduced cervical lordosis and severe FHP, it was reported that cervical lordosis increased while FHP decreased 11) .…”
Section: Discussionmentioning
confidence: 99%
“…All patients had FHP with 15 mm or larger anterior weight bearing (AWB) 10) in lateral views in plain radiography. Patients were seen at D Hospital in Korea between April and June 2012.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Recent randomized clinical trials (RCTs) of patients with neck pain have also reported minor adverse reactions in which HVLA SM and other manual therapies were used as the primary interventions. 7,8 The frequencies reported in these RCTs ranged from 9% to 28% for the most common reaction, increased neck pain.…”
Section: Introductionmentioning
confidence: 99%